Considerations on Protocol N°16: Can the New Advisory Competence of the European Court of Human Rights Breathe New Life into the European Convention on Human Rights?. Issue 2 (6th May 2015) - Giannopoulos, Christos
Abstract : Protocol n°16 expands the advisory jurisdiction of the European Court of Human Rights (hereinafter ECtHR) by introducing a mechanism of litigation-related opinions ( "avis contentieux" ). It affords the highest national courts and tribunals the ability to ask the ECtHR for an advisory opinion on questions of principle related to the interpretation and application of the rights and freedoms defined in the European Convention on Human Rights (hereinafter Convention) and the Protocols thereto.